A Dose Escalation Study of Trientine Plus Carboplatin and Pegylated Liposomal Doxorubicin in Women With a First Relapse of Epithelial Ovarian, Tubal, and Peritoneal Cancer Within 12 Months After Platinum-Based Chemotherapy - Huang, Yu-Fang; Kuo, Macus Tien; Liu, Yi-Sheng; Cheng, Ya-Min; Wu, Pei-Ying; Chou, Cheng-Yang (Frontiers in Oncology, 2019)
Epithelial ovarian cancer (EOC) is the leading cause of gynecological cancer-related deaths worldwide. Preclinical studies found that copper-lowering agents could re-sensitize platinum-resistant cancer cells by enhancing the human copper transporter 1 (hCtr1)-mediated uptake of platinum. In the clinic, re-sensitization of platinum-resistance in relapsed EOC has been discovered by the application of trientine plus platinum [NCT01178112]. However, no pharmacokinetic data of trientine has been reported in cancer patients. Our study aimed to explore the safety and activity of trientine combined with carboplatin and pegylated liposomal doxorubicin (PLD) in patients with EOC, tubal, and peritoneal cancer who experienced disease progression during platinum-based chemotherapy or showed relapse <12 months after completing first-line chemotherapy. Also, we aimed to demonstrate pharmacokinetic parameters and to discover potential biomarkers in our EOC patients. In this dose escalation study, 18 Asian patients in six dosing cohorts received fixed doses of carboplatin (AUC 4) and PLD (LipoDox®, TTY Biopharm Co. Ltd., Taipei, Taiwan) (40 mg/m2, day 1 per 4-week cycle) and escalated daily trientine doses (range: 300–1800 mg; initiated 7 days before the 1st combination cycle) according to a 3 + 3 design. No dose-limiting toxicity or treatment-related death was observed. Four patients (22.2%) developed grade 3 drug-related adverse events (AEs), whereas no grade 4 AEs were encountered. Anemia and grade 2 dizziness were the most common hematological toxicity and neurotoxicity, respectively. In a pharmacokinetics comparison with healthy volunteers in the literature, our patients achieved greater absorption after oral trientine and more rapid elimination of triethylenetetramine dihydrochloride at high doses. The clinical benefit rate was 33.3% and 50.0% in the platinum-resistant and the partially platinum-sensitive group, respectively. A high baseline serum iron level and low serum copper level might help differentiate subgroups of patients with different clinical responses. Nevertheless, no associations of the clinical response with the levels of serum hCtr1, ceruloplasmin, or copper were observed. Combination therapy with carboplatin, trientine, and PLD was well tolerated and safe. Our results encourage the development of a future phase II trial. Clinical trial registration: ClinicalTrials.gov # NCT03480750